Quinolone-3-Diarylethers: A New Class of Antimalarial Drug - Aaron Nilsen; Alexis N. LaCrue; Karen L. White; Isaac Forquer; R. Matthew Cross; Jutta Marfurt; Michael W. Mather; Michael J. Delves; David M. Shackleford; Fabián E. Saénz; Joanne M. Morrisey; Jessica Steuten; et al. (2013)
ELQ-300, an investigational drug for treating and preventing malaria, shows potent transmission-blocking activity in rodent models of malaria.